The Structure of Graphic Narration in the two volumes Al-Sayyab (The Blind Prostitute and the Grave Digger (Journal of the College of Basic Education, 2022)
The sense of the necessity of narration as a construction technique combined with the structure of the neighboring structures in the formation of the structure of literary discourse, especially poetic it did not stop the consciousness of the poet renewed and eager to offer a creative breakthrough in which he settled in the literary taste of the building of the art of poetry inherited, (I am an epic poet and a long poem)) in the presence of more than a textual function to support our claims, both sexes literary are not without the element of narratives which appear in them form a milestone cannot be skipped or exceeded technically. In this study, we seek to deduce the nature of the internal structure of narrative structure in the narrative / poetic narrative, which is what we have called the "narrative narrative", in which we mean the narratives that are shown by the picture sequences of frequency and image accumulation. Within the poetic fabric, the whole form of a narrative unit that codifies the thematic dimensions of the poem, thus creating a textual amplification and linguistic implications that explore the emotion of the poet and characterize them during those narrative images. The narrative narrative is a linguistic utterance that is done by forming the image, meaning that the image possesses a narcotic soul Wei is an incident, it is a narrative in which the storyteller mixes with lyricism and poeticism, and thus the narrative narrative is a narrative that can be deduced and borrowed from poetic imagery.